Charleso Martindale’io recepcijos teorija ir antikinė literatūra - Dikmonienė, Jovita (Literatūra, 2007)
This article in the descriptive style introduces with adaptation of hermeneutics of reception to Latin poetry in Charles Martindale’s book “Redeeming the text: Latin poetry and the hermeneutics of reception”. The following five ideas of Martindale’s reception theory are 1) a contingent and continuously supplemented understanding of the meaning of the text being read, 2) continuously (re)interpreted contexts, 3) history as intersubjective stories about the past, 4) doubting the radical canon criticism, and 5) a dialogue with classical texts. Martindale argues that the text does not have any fixed meaning given by the author. On this stance, he does not agree with Jauss and Gadamer. Martindale compares interpretation of a literary work to performance of a piece of music: each new reading of the same text becomes a new concretization” and differs from any other manner of reading. Martindale notes that when studying ancient literature we cannot approach the pure, non-interpreted facts. Different people interpret one and the same fact differently, depending on their values, experience, and interests. Martindale does not agree with Fish’s theory of interpretative communities, arguing that only the critic himself hides behind the “implied reader” construction. He agrees with theories of dialogue of Bakhtin and Gadamer, with Derridean deconstruction. Martindale suggests understanding reading as an acquaintance and dialogue with the author of the text, which is influenced by the différance. Such a dialogue actualises the ancient literary work and enables passing it on to future generations.